Poisoning in the Modern World New Tricks for an Old Dog? - Karcioglu, Ozgur; Arslan, Banu (IntechOpen, 2019)
Over 400 years ago, Swiss alchemist and physician Paracelsus (1493-1541) cited: "All substances are poisons; there is none that is not a poison. The right dose differentiates a poison from a remedy." This is often condensed to: "The dose makes the poison." So, why are we overtly anxious about intoxications?In fact, poisons became a global problem with the industrial revolution. Pesticides, asbestos, occupational chemicals, air pollution, and heavy metal toxicity maintain high priority worldwide, especially in developing countries. Children between 0 and 5 years old are the most vulnerable to both acute and chronic poisonings, while older adults suffer from the chronic effects of chemicals. This book aims to raise awareness about the challenges of poisons, to help clinicians understand current issues in toxicology.